Effects of thiopental, propofol and alfaxalone on laryngeal motion during oral laryngoscopy in healthy dogs - Zeiler, Gareth Edward (University of Pretoria, 2017)
Mini Dissertation (MMedVet)--University of Pretoria, 2016.